Maintenance system and body size of swamp buffalo (Bubalus bubalis) in Gunung Toar and Cirenti districts, Riau Province - Larasati, Kania; Yendraliza, Yendraliza; Handoko, Jully; Febriyanti , Rahmi (Fakultas Peternakan Universitas Papua, 2025)
The body dimensions of livestock are not only influenced by genetic factors but also shaped by environmental conditions and livestock management practices implemented by farmers. This study aims to analyze the characteristics of buffalo farmers, the management systems, and the body dimensions of buffaloes in Gunung Toar and Cirenti Districts. The research was conducted using a survey method, involving 120 farmers as respondents. Measurements were taken on 50 male and 300 female buffaloes. The study examined farmer characteristics, livestock management systems, and buffalo body dimensions. Data were analyzed using mean and standard deviation, while differences between the two districts were assessed using t-tests. The findings revealed that most buffalo farmers inherited the profession, were predominantly male, had an education level ranging from elementary to high school, were over 50 years old, and had over 16 years of livestock experience, typically without receiving livestock extension services. The livestock management systems in both districts were similar, with a 22-22.5% maintenance rate. However, the chest circumference of buffaloes in the Gunung Toar District was greater than that in the Cirenti District. In conclusion, the livestock management practices covering housing, breeding, feeding, and health were still inadequate, ranging from 20% to 50% in quality. The buffaloes in the Gunung Toar District exhibited larger chest circumferences than those in the Cirenti District.